Design of an analytical solution for the reduction of supply chain losses in the context of international logistics - Mezerová, Veronika; Potančok, Martin; Bothe, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
This paper is focusing on delivering practical solution for solution of business problem with low visibility and cost control in supply chain in context of international container logistics, it provides end-to-end implementation self-service BI environment using Microsoft Power BI tool, Microsoft Power Query and Microsoft O365 tools. It provides practical project methodology for overall project delivery, general approach for implementation of data governance model, approaches to design reports and dashboards and effective set up od data architecture with focus on maximum usage of existing tools and resources. Main goal is to implement reporting and analytic solution that will enable data driven decision making and increase productivity of the users that will enable more focus on root cause analysis and implementation of preventive measures. Partial goals of the project are also to document data sources and processes in the area, set up of governance model proposal and identification of further process improvements. Outcome of the project is evaluated by satisfaction of key business stakeholders with delivered solution.
Vedoucí práce: Martin Potančok
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet